FOOD SAFETY STUDY: A PRELIMINARY ANALYSIS OF ORGANOLEPTIC AND TOTAL PLATE COUNT IN MEAT OF CHANNOS CHANNOS’ OBTAINED FROM TRADITIONAL POND FARMING - Kartikaningsih H.; Djamaludin H.; Yahya; Putri A.S.D.; Trisnanda R.W. (Russian Journal of Agricultural and Socio-Economic Sciences)
Final Disposal Sites as the final place of waste processing that implements the open dumping system have the risk of environmental pollution. Leachate comes from the results of decomposition or degradation of decomposed and dissolved waste. The presence of leachate content also has a negative impact on the environment, especially on the decline in water quality and disruption of the metabolism of aquatic organisms. The environment of traditional Channos channos ponds has the potential to be contaminated by leachate. This study was conducted by taking samples of pond water and farmed C. channos by sampling in 3 different zones. Zone 1 ponds were within a radius of less than 1 kilometer, zone 2 was within a radius of 1 to 2 kilometers and zone 3 was in the zone near the sea within a radius of more than 2 kilometers from the landfill. The research procedure carried out was total bacterial contamination tests. Based on the results of study, C. channos in zone 1 have a higher total bacterial value compared to zones 2 and 3. This is related to the pond area in zone 1 having the closest radius from the site, which is less than 1 kilometer. However, the total plate count in fish meat samples from zones 1, 2, and 3 exceeds the safety threshold for fresh fish food. The presence of bacterial contamination that exceeds the standard limit can have a negative effect on consumers. Therefore, it is important to know the safety of food before consuming food so that the body is protected from toxins from food sources.